The Implementation of the Jigsaw-Type Cooperative Learning Model to Enhance Students’ Motivation and Participation in Physical Education - Zainal Widyanto; Rif'iy Qomarrullah; Soni Tebai (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2025)
This study addresses the low levels of student motivation and participation commonly observed in physical education classes. Traditional teacher-centered methods often fail to engage all students, resulting in passive learning environments. To overcome this challenge, the Jigsaw-type cooperative learning model was implemented to encourage active student involvement and boost learning enthusiasm. The research was conducted in a junior high school setting, targeting eighth-grade students as the object of study. The primary aim of this research is to examine the effectiveness of the Jigsaw cooperative learning model in increasing students’ motivation and participation during physical education lessons. A classroom action research design was employed, involving two cycles with stages of planning, implementation, observation, and reflection. Data were collected through observation sheets, student questionnaires, and teacher field notes, and then analyzed descriptively. The results indicate a significant improvement in both student motivation and participation from the first to the second cycle. In the initial observation, student participation was limited, and motivation levels were low. However, after the implementation of the Jigsaw method, students demonstrated increased engagement, collaboration, and enthusiasm in physical activities. In conclusion, the Jigsaw-type cooperative learning model proves to be an effective instructional strategy to enhance students’ motivation and participation in physical education. This approach not only fosters a more interactive learning environment but also supports the development of social and teamwork skills among students.